2019
DOI: 10.1016/j.fertnstert.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and rheumatologic causes and treatment of recurrent pregnancy loss: what is the evidence?

Abstract: Disclaimer: Authors for ''fertile battles'' are chosen to represent the full breadth of opinions. Individual authors, even within one side of the debate, do not necessarily agree with all viewpoints expressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 91 publications
0
15
0
3
Order By: Relevance
“…Vast studies on unexplained RSA (URSA) suggested potential immunologic modification, containing underlying autoimmune inflammation [ 154 ]. Aspirin, low molecular weight heparin (LMWH), and an association of them have been applicated in research for URSA as treatments.…”
Section: Treatment Of Recurrent Spontaneous Abortionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vast studies on unexplained RSA (URSA) suggested potential immunologic modification, containing underlying autoimmune inflammation [ 154 ]. Aspirin, low molecular weight heparin (LMWH), and an association of them have been applicated in research for URSA as treatments.…”
Section: Treatment Of Recurrent Spontaneous Abortionmentioning
confidence: 99%
“…There is an evident case of an autoimmune progress result in RSA that combination therapy with low-dose aspirin and prophylactic heparin or LMWH could bring better pregnancy outcomes in patients with antiphospholipid syndrome, which has been taken as a standard therapeutic method for female meeting standard for obstetric antiphospholipid syndrome [ 157 ]. Furthermore, an existing evidence suggested that immunological therapeutic method had a positive role in RSA [ 154 ]. A variety of immunotherapies have become available, covering intravenous immune globulin (IVIG), immunosuppressant, and granulocyte colony-stimulating factor [ 158 , 159 ].…”
Section: Treatment Of Recurrent Spontaneous Abortionmentioning
confidence: 99%
“…Частота НВ складає від 15 до 23%, причому в половині випадків відзначають звичне НВ. Окрім цього, переривання вагітності в 75-80% випадків настає на ранніх строках (до 12 тижнів гестації) [1][2][3]21]. Основні труднощі, пов'язані з вивченням НВ, обумовлені поліетіологічністю цієї патології, в розвитку та реалізації якої беруть участь важливі системи організму матері й плода.…”
Section: вступunclassified
“…This topic remains controversial in the literature and at scientific events, such as the one that occurred in the “Fertile Battles” section of the recent edition of Fertility and Sterility, the official journal of American Society for Reproductive Medicine (ASRM). The key point of the debate was to understand the immunological mechanisms involved in the embryonic implantation and thus propose therapeutic options based on the clinical evidence of improvement in pregnancy results 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, clinicians and patients expect that immunotherapies, with strong scientific evidence, can help a considerable percentage of couples with RM and recurrent implantation failure (RIF). However, the diagnosis of RM and RIF remains unclear and inconsistent, when evaluated established protocols 1 …”
Section: Introductionmentioning
confidence: 99%